ACTUALIZACION DE LOS NOMBRES DE CLERIDOS (COLEOPTERA: CLERIDAE) EN LA OBRA DE CLAUDIO GAY - Solervicens, Jaime (Acta Entomológica Chilena, 2022)
The taxonomic and nomenclatura! status of Chilean Clerid beelles taxa desrribed in Gay's Historia Física y Política de Chile is modernized and actualized in this paper.